What Destination Awaits the Development of Botswana: The Sharp Edges of Diamond Dependency: Some Political Economy Considerations - Muth, Daniel (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
Botswana has long been lauded for developing uniquely strong political institutions and using its diamond revenues productively to enhancing the welfare of its citizens. However, depleting diamond sources conjoined with an inadequate level of economic diversity poses serious challenges to further development. Unequivocally, the country has arrived at a crossroads. Botswana must seize the narrow window of time before its diamond resources are depleted, by nurturing economic sectors and investing in human capabilities, in order to climb higher on the ladder of economic development. If they do not, the country may be set back dramatically after decades long successful policy efforts. This essay addresses the puzzle of why the development of Botswana has suddenly stagnated despite having powerful facilitating factors such as political stability and advanced economic policies. This essay will shed some light on the dilemma by discussing key political economy developments driven by the diamond dependency, and the way in which Botswana is integrated into regional markets. Current policy deliberations should be informed by a greater understanding of the main factors affecting past developments. Therefore, my aim is to contribute to the ongoing debate on the structural conditions affecting develop- mental outcome in the region, and to reinvigorate the discussion on possible policy solutions to mitigate/overcome contingency.